Preparation method and application of reduced-state methyl glycolate catalyst
The preparation of a mixture of nano-scale CuAg complex and SiO2 by chemical precipitation method solves the problem of unstable activity and low selectivity of the existing catalyst preparation method at low temperatures, and achieves efficient and stable preparation of methyl glycolate.
Patent Information
- Application Number
- CN202411762236.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-02-25
AI Technical Summary
The existing catalyst preparation methods have problems such as unstable activity, low selectivity, and complex process in industrial production, making it difficult to efficiently prepare methyl glycolate at low temperatures.
A mixture of nano-scale CuAg complex and SiO2 was prepared by chemical precipitation method, and the uniform dispersion of the active components was ensured by the use of surfactant, and chemical reduction was performed on a room temperature by reducing agent of sodium borohydride to form a stable Cu+/(Cu0+Cu+) ratio.
The catalyst is achieved with high activity, high selectivity and high stability. The conversion rate of dimethyl oxalate can be greater than 99%, the selectivity of methyl glycolate is greater than 92%, there are few reaction by-products, and the target product is easy to separate.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of catalyst preparation, in particular to a preparation method and application of a reduced methyl glycolate catalyst. Background Art
[0002] Methyl glycolate (MG) has the properties of both alcohol and ester. It is widely used in the pharmaceutical and chemical fields and is an important organic intermediate. At present, the main industrial synthesis methods of methyl glycolate are: formaldehyde carbonylation, methyl formate coupling, chloroacetic acid esterification, and hydrogenation after synthesis gas preparation of dimethyl oxalate (DMO). The previous methods have problems such as heavy pollution, strong corrosiveness, and low yield. In view of the relative economy and environmental protection of the synthesis gas route and the main position of coal resources in my country's energy structure, the process of preparing MG by hydrogenation of DMO has better industrial application prospects and economic benefits.
[0003] The development of hydrogenation catalysts is currently the focus of research on the DMO hydrogenation to MG reaction. Traditional copper-based catalysts are cheap and easy to make, and have high hydrogenation activity in the DMO hydrogenation reaction, but the intermediate product MG is easily further hydrogenated to produce ethylene glycol (EG), that is, the hydrogenation product is mainly EG (the yield of MG is less than 10%); the introduction of the additive Ag inhibits the hydrogenation activity of Cu, thereby improving the selectivity of MG.
[0004] Patent CN114054041 discloses a hydrogenation catalyst with copper as the main active component, which is prepared by ammonia evaporation and impregnation, and the MG selectivity can reach 99%. It can be concluded from the examples that the catalyst preparation process is relatively complicated. Moreover, the biggest problem of the ammonia evaporation method is that the catalyst structure and activity are easily affected by the ammonia evaporation temperature. The local overheating of the mixture that may exist during the preparation process will greatly reduce the catalyst activity, causing the catalyst performance to be very unstable. Patent CN101138730A discloses a simple and easy Cu-Ag / SiO2 catalyst by impregnation, but the maximum DMO conversion rate of the catalyst is 85%, and the selectivity of methyl glycolate is 83%. The catalyst is prepared by impregnation, and the dispersion of its active components is not high. Affected by the water absorption rate of the active components and the carrier, it is difficult to increase the loading amount of the active components. Patent CN113856700A uses a sol-gel method to prepare a hydrogenation catalyst. After gel aging, alkaline solution solidification, washing evaporation and roasting reduction, the preparation process is complicated and it is difficult to industrialize production.
[0005] The above-mentioned preparation methods all have various problems in industrial production. Therefore, how to design a catalytic system that can catalyze the hydrogenation of dimethyl oxalate to prepare methyl acetate with high activity, high selectivity and high stability at a relatively high temperature is still a problem that needs to be solved urgently. Summary of the invention
[0006] The purpose of the present invention is to solve the above technical problems and to provide a multi-component hydrogenation catalyst for synthesizing methyl glycolate in a reduced state with low cost, high low-temperature activity, good thermal stability, stable metal grain size and easy industrialization and a preparation method thereof.
[0007] A method for preparing a reduced methyl glycolate catalyst comprises the following steps: (1) Dissolve water glass in 60°C water, add surfactant, and then add dilute acid until the pH of the solution is 8-9, forming a white precipitate A; (2) dissolving a soluble copper salt and a soluble silver salt in water, then adding polyvinyl pyrrolidone and stirring until all are dissolved to obtain a solution B; (3) Add solution B to solution A, add sodium borohydride, stir at room temperature, react for 0.5 to 1 hour, and obtain a mixture of nano-scale single element Cu and Ag complex and SiO2. Wash, filter, dry, calcine, and shape.
[0008] Preferably, the mass ratio of water glass, soluble copper salt and soluble silver salt is 100:(3.2-16.8):(0.13-1.3).
[0009] Preferably, the added amount of the surfactant is 0.15% to 0.5% of the mass of the water glass; the added amount of the polyvinyl pyrrolidone is 2% of the mass of the water glass; and the added amount of the sodium borohydride is 1.2% to 6.4% of the mass of the water glass.
[0010] Preferably, the catalyst prepared by the preparation method has a specific surface area of 800 to 950 m 2 / g.
[0011] Preferably, the modulus of the water glass is 2.0-3.3, and the concentration of the water glass is 15-25%.
[0012] Preferably, the surfactant in step (1) is one or more of polyvinyl pyrrolidone, ethylenediaminetetraacetic acid, and hexadecyltrimethylammonium bromide.
[0013] Preferably, the dilute acid in step (1) is dilute sulfuric acid, dilute hydrochloric acid or dilute phosphoric acid.
[0014] Preferably, the soluble copper salt in step (2) is copper nitrate, copper acetate, copper chloride or copper sulfate; and the soluble silver salt is silver nitrate.
[0015] Preferably, the calcination in step (3) is carried out in a nitrogen atmosphere at a temperature of 450-500°C for 5 hours, and the drying is carried out in a nitrogen atmosphere at a temperature of 120°C for 5 hours.
[0016] The invention discloses an application of a reduced methyl glycolate catalyst, wherein the catalyst is used for preparing methyl glycolate from dimethyl oxalate.
[0017] Beneficial effects of the present invention: 1. This method synthesizes CuAg nanoparticles by chemical reduction at room temperature. The reducing agent sodium borohydride is used to reduce Cu 2+ / Ag + The active component copper was reduced to Cu and Cu + At the same time, the uniformity of the final catalyst particles is ensured by the combined use of surfactants, and the double protection greatly improves the recycling performance of the catalyst. In addition, in the traditional hydrogen reduction process, Cu + Easily reduced to Cu 0 , resulting in the Cu + / Cu0 is out of balance, resulting in catalyst deactivation. The present invention adopts a special reduction process, during which Cu is reduced to Cu and Cu + , which can maintain a stable Cu + / (Cu 0 +Cu + ) ratio, so that the performance of the hydrogenation agent remains stable; 2. This paper provides a simple preparation process, using chemical precipitation method to prepare a highly dispersed hydrogenation catalyst with small particle size, large specific surface area, honeycomb porous structure, and nano-scale active components; 3. The catalyst for preparing methyl glycolate by hydrogenating dimethyl oxalate of the present invention has high activity, good stability and high selectivity. The conversion rate of dimethyl oxalate can be greater than 99%, the selectivity of methyl glycolate is greater than 92%, the reaction by-products are few, and the target product is easy to separate. DETAILED DESCRIPTION
[0018] Example 1 A method for preparing a reduced methyl glycolate catalyst comprises the following steps: (1) Dissolve 100 g of water glass with a modulus of 2.0 and a concentration of 15% in 70 ml of 60°C water, add 0.15 g of ethylenediaminetetraacetic acid, and then add 0.1 mol of dilute acid until the pH of the solution is 8-9, and a white precipitate A is generated; (2) Dissolve 3.2 g Cu(NO3)2.3H2O and 0.13 g AgNO3 in water, then add 0.2 g polyvinyl pyrrolidone and stir until all dissolved to obtain solution B; (3) Solution B is added to solution A, and 12 ml of 10% sodium borohydride solution is added. The mixture is stirred at room temperature and reacted for 0.5 to 1 h to obtain a mixture of nanoscale elemental Cu and Ag complexes and SiO2. The mixture is washed, filtered, dried at 120°C for 5 h under N2 protection, and calcined at 450°C for 5 h under nitrogen protection to form the mixture.
[0019] Example 2 A method for preparing a reduced methyl glycolate catalyst comprises the following steps: (1) Dissolve 100 g of water glass with a modulus of 3.3 and a concentration of 20% in 70 ml of 60°C water, add 0.2 g of ethylenediaminetetraacetic acid, and then add 0.13 mol of dilute HCl until the pH of the solution is 8-9, and a white precipitate A is generated; (2) Dissolve 4.3 g Cu(NO3)2.3H2O and 0.54 g AgNO3 in water, then add 0.2 g polyvinyl pyrrolidone and stir until all dissolved to obtain solution B; (3) Solution B is added to solution A, and 15 ml of 10% sodium borohydride solution is added. The mixture is stirred at room temperature and reacted for 0.5 to 1 h to obtain a mixture of nano-scale elemental Cu and Ag complex and SiO2. The mixture is washed, filtered, dried at 120°C for 5 h under N2 protection, and calcined at 470°C for 5 h under nitrogen protection to form the mixture.
[0020] Example 3 A method for preparing a reduced methyl glycolate catalyst comprises the following steps: (1) Dissolve 100 g of water glass with a modulus of 3.0 and a concentration of 20% in 70 ml of 60°C water, add 0.2 g of ethylenediaminetetraacetic acid, and then add 0.13 mol of dilute HCl until the pH of the solution is 8-9, and a white precipitate A is generated; (2) Dissolve 9.8 g Cu(NO3)2.3H2O and 0.61 g AgNO3 in water, then add 0.2 g polyvinyl pyrrolidone and stir until all dissolved to obtain solution B; (3) Add solution B to solution A, add 35 ml of 10% sodium borohydride solution, stir at room temperature, react for 0.5 to 1 h, and obtain a mixture of nano-scale elemental Cu and Ag complex and SiO2. Wash, filter, dry at 120°C for 5 h under N2 protection, and calcine at 470°C for 5 h under nitrogen protection to form the mixture.
[0021] Example 4 A method for preparing a reduced methyl glycolate catalyst comprises the following steps: (1) Dissolve 100 g of water glass with a modulus of 3.0 and a concentration of 25% in 70 ml of 60°C water, add 0.25 g of ethylenediaminetetraacetic acid, and then add 0.17 mol of dilute HCl until the pH of the solution is 8-9, and a white precipitate A is generated; (2) Dissolve 12.5 g Cu(NO3)2.3H2O and 1.3 g AgNO3 in water, then add 0.2 g polyvinyl pyrrolidone and stir until all dissolved to obtain solution B; (3) Solution B is added to solution A, and 48 ml of 10% sodium borohydride solution is added. The mixture is stirred at room temperature and reacted for 0.5 to 1 h to obtain a mixture of nano-scale elemental Cu and Ag complex and SiO2. The mixture is washed, filtered, dried at 120°C for 5 h under N2 protection, and calcined at 470°C for 5 h under nitrogen protection to form the mixture.
[0022] Example 5 A method for preparing a reduced methyl glycolate catalyst comprises the following steps: (1) Dissolve 100 g of water glass with a modulus of 3.0 and a concentration of 20% in 70 ml of 60°C water, add 0.2 g of ethylenediaminetetraacetic acid, and then add 0.13 mol of dilute HCl until the pH of the solution is 8-9, and a white precipitate A is generated; (2) Dissolve 13.0 g Cu(NO3)2.3H2O and 0.66 g AgNO3 in water, then add 0.2 g polyvinyl pyrrolidone and stir until all dissolved to obtain solution B; (3) Solution B is added to solution A, and 50 ml of 10% sodium borohydride solution is added. The mixture is stirred at room temperature and reacted for 0.5 to 1 h to obtain a mixture of nano-scale elemental Cu and Ag complexes and SiO2. The mixture is washed, filtered, dried at 120°C for 5 h under N2 protection, and calcined at 470°C for 5 h under nitrogen protection to form the mixture.
[0023] Example 6 A method for preparing a reduced methyl glycolate catalyst comprises the following steps: (1) Dissolve 100 g of water glass with a modulus of 3.0 and a concentration of 20% in 70 ml of 60°C water, add 0.2 g of ethylenediaminetetraacetic acid, and then add 0.13 mol of dilute HCl until the pH of the solution is 8-9, and a white precipitate A is generated; (2) Dissolve 16.8 g Cu(NO3)2.3H2O and 0.7 g AgNO3 in water, then add 0.2 g polyvinyl pyrrolidone and stir until all dissolved to obtain solution B; (3) Add solution B to solution A, add 64 ml of 10% sodium borohydride solution, stir at room temperature, react for 0.5 to 1 h, and obtain a mixture of nano-scale elemental Cu and Ag complex and SiO2. Wash, filter, dry at 120°C for 5 h under N2 protection, calcine at 500°C for 5 h under nitrogen protection, and shape.
[0024] Example 7 (1) Dissolve 100 g of water glass with a modulus of 3.0 and a concentration of 20% in 70 ml of 60°C water, add 0.3 g of polyvinyl pyrrolidone, and then add 0.14 mol of dilute H2SO4 until the pH of the solution is 8-9 and a white precipitate A is generated; (2) Dissolve 15 g Cu(CH3COO)2·2H2O and 0.73 g AgNO3 in water, then add 0.2 g polyvinyl pyrrolidone and stir until all dissolved to obtain solution B. (3) Solution B is added to solution A, and 50 ml of 10% sodium borohydride solution is added. The mixture is stirred at room temperature and reacted for 0.5 to 1 h to obtain a mixture of nano-scale elemental Cu and Ag complexes and SiO2. The mixture is washed, filtered, dried at 120°C for 5 h under N2 protection, and calcined at 470°C for 5 h under nitrogen protection to form the mixture.
[0025] Example 8 (1) Dissolve 100 g of water glass with a modulus of 3.0 and a concentration of 20% in 70 ml of 60°C water, add 0.28 g of polyvinyl pyrrolidone, and then add 0.13 mol of dilute H3PO4 until the pH of the solution is 8-9 and a white precipitate A is generated; (2) Dissolve 14.3 g CuCl2·5H2O and 0.7 g AgNO3 in water, then add 0.2 g polyvinyl pyrrolidone and stir until all dissolved to obtain solution B; (3) Add solution B to solution A, add 60 ml of 10% sodium borohydride solution, stir at room temperature, react for 0.5 to 1 h, and obtain a mixture of nano-scale elemental Cu and Ag complex and SiO2. Wash, filter, dry at 120°C for 5 h under N2 protection, calcine at 470°C for 5 h under nitrogen protection, and shape.
[0026] Example 9 (1) Dissolve 100 g of water glass with a modulus of 3.0 and a concentration of 20% in 70 ml of 60°C water, add 0.5 g of hexadecyltrimethylammonium bromide, and then add 0.12 mol of dilute H3PO4 until the pH of the solution is 8-9 and a white precipitate A is generated; (2) Dissolve 16.2 g CuSO4·5H2O and 0.71 g AgNO3 in water, then add 0.2 g polyvinyl pyrrolidone and stir until all dissolved to obtain solution B; (3) Add solution B to solution A, add 55 ml of 10% sodium borohydride solution, stir at room temperature, react for 0.5 to 1 h, and obtain a mixture of nano-scale elemental Cu and Ag complex and SiO2. Wash, filter, dry at 120°C for 5 h under N2 protection, calcine at 470°C for 5 h under nitrogen protection, and shape.
[0027] Comparative Example 1 No surfactant was added, and the rest was the same as in Example 5.
[0028] 10 g of the catalysts obtained in the above examples and comparative examples were respectively loaded into a tubular fixed bed reactor, and the prepared 0.2 g / ml methanol solution of dimethyl oxalate was introduced into the vaporization chamber and mixed with hydrogen to carry out oxalate hydrogenation reaction. The hydrogen pressure during the reaction was 2 MPa, the temperature was 180-195°C, H2 / DMO=100, and the liquid hourly space velocity of dimethyl oxalate was 1.0 h -1 The results are shown in Table 1: .
[0029] At the same time, the stability of the catalysts obtained in Examples 1-5 and the comparative example was evaluated, and the results are shown in Table 2: .
Claims
1. A method for preparing a reduced methyl glycolate catalyst, characterized in that: The following steps are involved: (1) Dissolve water glass in 60°C water, add surfactant, and then add dilute acid until the pH of the solution is 8-9, forming a white precipitate A; (2) dissolving a soluble copper salt and a soluble silver salt in water, then adding polyvinyl pyrrolidone and stirring until all are dissolved to obtain a solution B; (3) Add solution B to solution A, add sodium borohydride, stir at room temperature, react for 0.5 to 1 hour, and obtain a mixture of nano-scale single element Cu and Ag complex and SiO2. Wash, filter, dry, calcine, and shape.
2. The method for preparing the reduced methyl glycolate catalyst according to claim 1, characterized in that: The mass ratio of the water glass, the soluble copper salt and the soluble silver salt is 100:(3.2-16.8):(0.13-1.3).
3. The method for preparing the reduced methyl glycolate catalyst according to claim 1, characterized in that: The added amount of the surfactant is 0.15% to 0.5% of the mass of the water glass; the added amount of the polyvinyl pyrrolidone is 2% of the mass of the water glass; and the added amount of the sodium borohydride is 1.2% to 6.4% of the mass of the water glass.
4. The method for preparing the reduced methyl glycolate catalyst according to claim 1, characterized in that: The catalyst prepared by the preparation method has a specific surface area of 800 to 950 m 2 / g.
5. The method for preparing the reduced methyl glycolate catalyst according to claim 2, characterized in that: The modulus of the water glass is 2.0-3.3, and the concentration of the water glass is 15-25%.
6. The method for preparing the reduced methyl glycolate catalyst according to claim 1, characterized in that: The surfactant in step (1) is one or more of polyvinyl pyrrolidone, ethylenediaminetetraacetic acid, and hexadecyltrimethylammonium bromide.
7. The method for preparing the reduced methyl glycolate catalyst according to claim 1, characterized in that: The dilute acid in step (1) is dilute sulfuric acid, dilute hydrochloric acid or dilute phosphoric acid.
8. The method for preparing the reduced methyl glycolate catalyst according to claim 1, characterized in that: The soluble copper salt in step (2) is copper nitrate, copper acetate, copper chloride or copper sulfate; the soluble silver salt is silver nitrate.
9. The method for preparing the reduced methyl glycolate catalyst according to claim 1, characterized in that: The calcination in step (3) is carried out in a nitrogen atmosphere at a temperature of 450-500°C for 5 hours, and the drying is carried out in a nitrogen atmosphere at a temperature of 120°C for 5 hours.
10. An application of a reduced methyl glycolate catalyst, characterized in that: The catalyst is used for preparing methyl glycolate from dimethyl oxalate, and the catalyst is prepared according to the preparation method of claim 1.
Citation Information
Patent Citations
Catalyzer for oxalic ester hydrogenation synthesizing of glycolate and method of preparing the same
CN101138730A
Preparation method and application of copper-silver bimetallic catalyst
CN113856700A